Seed-Borne Fungal Diseases of Maize (Zea mays L.): A Review - Fazal ur Rehman; Muhammad Adnan; Maria Kalsoom; Nageen Naz; Muhammad Ghayoor Husnain; Haroon Ilahi; Muhammad Asif Ilyas; Gulfam Yousaf; Rohoma Tahir; Usama Ahmad (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2021)
Introduction: Maize (Zea mays) is one of the most important cereal crops. It is ranked as 3rd after wheat and rice. Due to its wide adaptability, diversified uses, and low production costs, it has great potential as a cereal crop. In the case of yield losses, various factors are involved. The fungal diseases of maize play a significant role in the reduction of both quantity as well as the quality of maize. Review Results: At the seedling stage, maize suffers from numerous diseases and many of them are seed-borne diseases. Anthracnose stalk rot (Colletotrichum graminicola), Charcoal rot of maize (Macrophomina phaseolina), Crazy top downy mildew disease (Sclerophthora macrospora), Corn grey leaf spot disease (Cercospora zeae-maydis), Aspergillus ear and kernel rot (Aspergillus flavus), Corn smut (Ustilago maydis), Southern corn leaf blight disease (Bipolaris maydis) etc. are important among these diseases.Chemical control of seed-borne pathogens of maize is rather difficult to achieve as a reasonably good. Due to the hazardous environmental effects of chemicals, the Integrated Management of the seed-borne fungal pathogens of corn is mostly preferred. The distribution, disease cycle, symptoms of the damage, effects of environmental factors, economical importance of disease, and integrated disease management options of major seed-borne fungal pathogens of maize have been reviewed in this review article from various currently available sources.